Barcoding alien invertebrates and biological control agents in South Africa, with a focus on the natural enemies of Thaumatotibia leucotreta (Meyrick) - Pitcher, Tristan (Department of Biological Sciences, 2026)
Alien invertebrate species and agricultural pests pose economic challenges through impeding crop production and threatening biodiversity in South Africa. Invertebrates are particularly successful invaders owing to their short generation times, high reproductive output, widespread occurrence across terrestrial, freshwater and marine environments, and considerable morphological diversity. The false codling moth, Thaumatotibia leucotreta (Meyrick), is a notable pest in South Africa, as it attacks important export crops such as citrus and stone fruit, greatly reducing returns on these exports, while threatening the country's access to international markets. While several wasp species have been recorded parasitising T. leucotreta, their distribution in South Africa is poorly documented, while only two species have been trialled as biological control agents against the pest. The projected shifts in species distribution patterns due to globalisation and climate change underscore the need for comprehensive baseline genetic and distribution data of alien invertebrate species and biological control agents. Such data are important for mitigating and managing biological invasions. A useful genetic tool in this respect, is DNA barcoding, which uses a short genetic marker to aid in the delimitation of species. However, there is no recent database of barcoded alien invertebrates and biological control agents in South Africa. In addition, thermal physiological traits of invertebrates are useful data for modelling species distributions, especially under climate change. However, current baseline physiological data of important pests and their biological control agents remain limited, negatively impacting our understanding of their present and future distribution patterns. This study aimed to: 1) review the DNA barcoding status of alien invertebrates and biological control agents in South Africa; 2) sample T. leucotreta parasitoid wasps in organic and IPM orchards within the Western Cape; and 3) to determine the critical thermal limits of Trichogrammatoidea cryptophlebiae Nagaraja, an egg parasitoid used as a biological control agent against T. leucotreta, in the laboratory. The review of alien invertebrate species in South Africa identified major gaps in DNA barcoding, particularly among arachnids and platyhelminths (flatworms). While 66.8% of all alien invertebrate species in the South African dataset were accessioned on BOLD (Barcoding of Life Datasystems), only 24.3% of these records represented specimens collected in South Africa. Furthermore, 44.6% of alien invertebrate species records on BOLD were not accompanied by images. This research has identified important gaps in the baseline knowledge of alien invertebrate species, pests, and biological control agents in South Africa. The paucity of South African specimens and image records on BOLD constrains the effectiveness of these records for identification. Despite conducting sampling under ideal conditions, no T. leucotreta parasitoids were sampled in the Western Cape. This absence may be attributed to low parasitoid population densities or suboptimal sampling methodology. The lack of T. leucotreta parasitoids sampled in the Western Cape suggests that natural wasp populations may be insufficient for pest control, supporting the case for augmentative biological control whilst highlighting the need for more intensive sampling and trials of parasitoid wasps as biological control agents. Using thermal tolerance assays, the critical thermal minimum and maximum of T. cryptophlebiae were determined to be 8.15°C ± 0.58°C and 44.50°C ± 0.41°C (mean ± SE), respectively. The critical thermal minimum of T. cryptophlebiae determined in this study exceeds the wasp's lower developmental threshold, indicating that adult wasps are less cold-tolerant than other life stages. These thermal tolerance data provide valuable baseline information for predicting potential distribution shifts of T. cryptophlebiae under climate change scenarios. Overall, this study contributed to baseline data on alien invertebrate, pest and biological control agent species, including T. leucotreta and its parasitoids, in South Africa. These baseline data underscore the need for further research on the distribution and biology of these important species.